Hospital laboratory management in dealing with disaster - Rosa Dwi Wahyuni; Syahrir A. Pasinringi; Sukri Palutturi; Muhammad Sabir; Diah Mutiarasari; Miranti; Mariani Rasyid; Haerani Harun; Rahma; Anwar Mallongi; Abd. Farid Lewa (Elsevier, 2021)
Objective: This study aims to identify scientific evidence and knowledge currently available related to clinical laboratory management in the face of disasters with the literature review method. Method: This is a literature review study. Various references were collected from online databases, including reports, scientific journals, and books in the last ten years. Articles are screened according to the research objectives. The keywords used are laboratories, hospitals, disasters, Point of Care Testing (POCT). Results: POCT is defined as the tools of a laboratory diagnostic test used in a disaster situation effectively. It can be operated by anyone who has been trained. However, it is quite constrained by temperature, earthquake shocks, and battery life. Storage and reagents supply, such as the strip test, might be prepare before the disaster. Moreover, maintenance and validation of POCT tools in disaster preparation is necessary. Hospitals must prepare POCT to conquer the limitation of electricity sources, human resources, and buildings situation was using a laboratory diagnostic analyzer not possible. The POCT was suitable to be conveyed anywhere both within the hospital and to disaster sites using the vehicle. Conclusion: POCT has the enormous potential as an emergency laboratory examination tool both at the hospital and at the disaster site to grip patient safety.